2016
DOI: 10.7324/japs.2016.60622
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, antibiotic and oil resistance pattern of some bacterial isolates from burns

Abstract: Infection is an important cause of mortality in patients with burns. Rapid emergence of hospital pathogens and antibiotic-resistant organisms necessitate periodic evaluation of bacterial colonization patterns and antibiogram sensitivity in burn wards. Sixty isolates from wounds of burns were collected from two hospitals in Cairo, Egypt along the period of 12 months in 2013. Antibiotic sensitivity of these isolates was assessed by single disk diffusion method. Multi drug resistance percentage and the most preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In 2013, we have collected P. aeruginosa strains throughout Cairo, Egypt, and the resistance levels to different antibiotics were determined. Data obtained revealed that the most majority of antibiotics (including carbapenems) have little to moderate effects which could give us a warning of the occurrence of outbreaks caused by this pathogen (Mabrouk et al, 2016). Ongoing a more detailed investigation was urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, we have collected P. aeruginosa strains throughout Cairo, Egypt, and the resistance levels to different antibiotics were determined. Data obtained revealed that the most majority of antibiotics (including carbapenems) have little to moderate effects which could give us a warning of the occurrence of outbreaks caused by this pathogen (Mabrouk et al, 2016). Ongoing a more detailed investigation was urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Reported effect of Ciprofloxacin against P. aeruginosa appeared to be damage to the peptidoglycan layer of the cell envelope. Various concentrations of Ciprofloxacin had already been shown to enhance bacterial uptake of antibacterial and to enhance antibacterial activity Polymyxin is known to damage cell envelope structures of both stationary and dividing cells (Newton 1954), and would be expected to have a similar [18], [19].…”
Section: Clinically Relevant Carbapenem Concentrationsmentioning
confidence: 99%